Internet use among youths and cyber wellness : implications on public education and policy making. - Lui, Li Ting. (2009)
There is widespread use of the Internet among Singapore youths. Of those aged 7-14 years, 90% are Internet users (IDA, 2007). As a result, there is increasing concern among educators and parents about the potential online risks our youths may be facing. This study uses a representative sample of Secondary 1 to 3 students to assess the current state of cyber wellness among Singaporean youths. Four focus groups were subsequently conducted to get feedback on current cyber wellness educational programs. Findings have shown that most, but not all of the youths take steps to protect their online safety. There are still a substantial number of youths who are putting themselves at risk of online dangers. In addition, our study found that one in four youths were victims of cyber bullying. We have come up with several policy and promotional recommendations to address these issues so that youths will be able to harness the benefits of the Internet while staying safe.